ЛІ ЦІНЧЖАО. ГЛАВИ III–V / ПЕРЕКЛАД З КИТАЙСЬКОЇ, ВСТУПНА СТАТТЯ ТА КОМЕНТАРІ Г. В. ДАЩЕНКО. - Dashchenko, Hanna (World of the Orient, 2025)
This publication presents the Ukrainian translation of chapters III–V (episodes 29–57) of the historical novel “Li Qingzhao” (“李清照”) written by the Hong Kong writer Nan Gongbo (南宮 搏, 1924–1983). These episodes were published from May 25 to June 21, 1960 in Taiwan in the Central Daily News (中央日報). This part of the novel describes Li Qingzhao’s life in Bianjing, the Song capital, between 1105 and 1113. The events of the private life of the protagonist’s aristocratic family are depicted against the backdrop of internal political struggle. Thanks to this, the author manages to show the dependence of literary processes on the balance of power in the Song society. The key element of the novel’s composition is shi and ci poetry written by Tang and Song poets, which Nan Gongbo used as a basis for the plot. These episodes include six full Song ci poems (by Zhou Banyan and Li Qingzhao) as well as the certain lines from Tang shi (by Yuan Zhen) and Song ci poems (by Liu Yong and Li Qingzhao). The introductory article presents the artistic and compositional features of this part of the novel. The notes provide explanations of terms and realities as well as brief information about historical characters mentioned in the text.